АЛГОРИТМ ФОРМИРОВАНИЯ ЗАДАННОГО ПОТОКОСЦЕПЛЕНИЯ В СИСТЕМАХ ВЕКТОРНОГО УПРАВЛЕНИЯ АСИНХРОННЫМИ ДВИГАТЕЛЯМИ В РЕЖИМЕ ОСЛАБЛЕНИЯ ПОЛЯ ДЛЯ ТРАНСПОРТНЫХ ПРИМЕНЕНИЙ - Воронко, А.Б. (Інститут електродинаміки НАН України, Київ, 2014)
An algorithm of flux reference forming in field weakening region for vector control systems of induction motor for traction application is developed. The proposed solution can effectively limit the stator voltage at a predetermined level, according to the DC-bus voltage of supply converter. Presented experimental results confirm the effectiveness of the proposed algorithm. References 6, figure 1.